In Vitro Preliminary Study On Perforation By Stripping In Curved Canals - Ionela Elisabeta Ciobanu; Andreea Cristiana Didilescu; Alexandru Andrei Iliescu; George Adrian Ciobanu; Andrei Iliescu (Romanian Society of Oral Rehabilitation, 2013)
The aim of the study was to assess the perforation by stripping after endodontic treatment with stainless steel (SS) and Ni-Ti manual instruments. 65 resin blocks have been prepared using the circumferential filing method with unprecurved 0.02-tapered SS and Ni-Ti K-files and then photographed with a stereomicroscope. The angle and the radius of the canal curve following instrumentation and the transportation distance of the curvature inner wall were measured at 5 and 8 mm from the apex. At 8mm, SS size 40 performed a -2.2 transportation compared to the sample. At 5mm, sizes 35 and 40 recorded modifications after both techniques, translated by an increase of the internal diameter. There were significant differences related to the curvature radiuses achieved both by SS files 35 and 40 and Ni-Ti size 40 by an increase compared to the sample's curvature radius (P<0.05). The stripping risk appears both in stainless steel and Ni-Ti files when large sizes are used.